Strategi Pengembangan Usaha pada UMKM Bakoel Barokah Kelurahan Gunung Sari Ulu Balikpapan - Dian Saripujiana; Alenci Najla Razita Putri; Dea Ananda S; Michelle Longkutoy (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
Micro, Small, and Medium Enterprises (MSMEs) often experience difficulties in product marketing, difficulties in reaching customers and lack of innovation. To develop MSMEs, product innovation and awareness of modern social media technology are needed. Many MSME actors are still lagging behind in utilizing technology, which has an impact on limited marketing and business development. The author of this Community Service research focuses on MSME Bakoel Barokah in Guning Sari Ulu Village, Balikpapan. MSME Bakoel Barokah owned by Ibu Alam faces obstacles in product development and marketing, especially in label design, packaging, and utilization of social media. Their products are only produced based on consumer orders. The researcher found the potential for Bakoel Barokah to develop better with innovation in labels, packaging, and digital marketing strategies through Instagram and WhatsApp.